The Influence of Leadership Style, Work Environment, End Work Motivation on Employee Performance at The Wonogiri Regency Disport Office - Fiki Hendro Yunanto; Sri Wijiastuti; Zandra Dwanita Widodo (International Journal of Economics and Management Sciences, 2024)
This research aims to determine the influence of Leadership Style, Work Environment, and Work Motivation on the Performance of Wonogiri District Dispora Office Employees, both partially and simultaneously. This research is quantitative using primary and secondary data. Data quality analysis testing uses validity tests and reliability tests. This research uses a survey method by distributing questionnaires. From a population of 32 people, all were sampled using saturated sampling techniques. The analysis used is multiple linear regression. This research shows that Leadership Style partially influences employee performance by 35.1%. The work environment partially influences employee performance by 14.7%. And Work Motivation partially influences employee performance by 20.2%. Leadership style, work environment, and work motivation simultaneously or together also have an influence on employee performance, shown by a significant value of 0.000 < 0.05. Meanwhile, the coefficient of determination test results have an Adjusted R Square value of 92.80%, which means that employee performance variables are influenced by leadership style variables, work environment, work motivation and the remaining 7.208% are influenced by other variables.